2016
DOI: 10.11591/ijeei.v4i1.198
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Stabilization of a Wind Turbine with STATCOM Using Intelligent Control Techniques

Abstract: Application of FACTS controller called Static Synchronous Compensator STATCOM to improve the performance of power grid with Wind System is investigated. The essential feature of the STATCOM is that it has the ability to absorb or inject fastly reactive power with power grid. Therefore the voltage regulation of the power grid with STATCOM FACTS device is achieved. Moreover restoring the stability of the wind system at suddenly step up or down in wind speed is obtained with STATCOM. This paper describes a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Where ρ is the air density, A is the turbine blade sweep area and V w is the wind speed. If the friction be neglected, mechanical characteristics of a turbine can be obtained as Equation (2)(3)(4).…”
Section: Description Of Wind Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…Where ρ is the air density, A is the turbine blade sweep area and V w is the wind speed. If the friction be neglected, mechanical characteristics of a turbine can be obtained as Equation (2)(3)(4).…”
Section: Description Of Wind Turbinementioning
confidence: 99%
“…Because of significant progress in the semiconductor devices and power electronics techniques, wind power becomes much more attractive in electrical power systems [2]. By using the methods of maximum power point tracking for conversion systems of wind-turbine energy, efficiency of wind-turbine generators is increased [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Neural network (NN) technique can handle efficiently the multi-input multi-out control system. Thus, the artificial neural network technique can be utilized to develop the controller for the D-STATCOM, DVR and UPQC to compensate different voltage and current related power quality problems [53] [68] [108], [115], [138], [150], [220].…”
Section: Neural Network (Nn) Based Theorymentioning
confidence: 99%
“…The role of FACTS devices in enhancing the stability of gridconnected wind power systems has been enumerated in detail [6]. Fuzzy logic and ANFIS-based control for the STATCOM in a grid-connected PMSG-based wind power system was proposed [7]. AnLuo,et al suggested a fuzzy-PI independent control technique for STATCOM in distribution networks [8].…”
Section: Introductionmentioning
confidence: 99%